Gender Contestation of CEO Narcissism in Earnings Management Practice - Nurfitri, Nurfitri; Jati, Fatma Dwi; Firdaus, Mohammad Iqbal (Jurnal Akuntansi Aktual, 2025)
Purpose: This research aims to examine whether the narcissistic CEO tends to be involved in high earning management, and gender as the variable of moderation. Method: Our research was done in the manufacturing companies of food and beverages sub-sectors listed in BEI in 2015 - 2020. The quantitative method was used to analyze the regression model of panel data. Findings: The result showed that there was a negative correlation between narcissistic CEO and earning management. In this case, the female CEO strengthened its negative correlation result. The period of our research indicated that CEO tends to do upward earning management. However, both male and female CEOs were also involved in the earning management through increasing or decreasing benefits. The higher narcissistic CEO level was not only involved in the high earning management but was also involved in the low earning management. Originality/Value: This research contributes to exploring the moderating influence of gender on the relationship between CEO narcissism and earnings management practices from the perspective of upper echelon theory. Furthermore, this research provides insight for investors to not only consider company earnings but also other factors such as CEO characteristics.